Downregulation of Bach1 protects osteoblasts against hydrogen peroxide-induced oxidative damage in vitro by enhancing the activation of Nrf2/ARE signaling. (25th August 2019) - Tian, Xiaoning; Cong, Fei; Guo, Hua; Fan, Jinzhu; Chao, Gao; Song, Tao
Abstract: Oxidative-stress-induced osteoblast dysfunction plays an important role in the development and progression of osteoporosis. BTB and CNC homology 1 (Bach1) has been suggested as a critical regulator of oxidative stress; however, whether Bach1 plays a role in regulating oxidative-stress-induced osteoblast dysfunction remains unknown. Thus, we investigated the potential role and mechanism of Bach1 in regulating oxidative-stress-induced osteoblast dysfunction. Osteoblasts were treated with hydrogen peroxide (H2 O2 ) to mimic a pathological environment for osteoporosis in vitro . H2 O2 exposure induced Bach1 expression in osteoblasts. Functional experiments demonstrated that Bach1 silencing improved cell viability and reduced cell apoptosis and reactive oxygen species (ROS) production in H2 O2 -treated cells, while Bach1 overexpression produced the opposite effects. Notably, Bach1 inhibition upregulated alkaline phosphatase activity and osteoblast mineralization. Mechanism research revealed that Bach1 inhibition increased the activation of nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) signaling and upregulated heme oxygenase 1 and NAD(P)H:quinone oxidoreductase 1 mRNA expression. The Bach1 inhibition-mediated protective effect was partially reversed by silencing Nrf2 in H2 O2 -exposed osteoblasts. Taken together, these results demonstrate that Bach1 inhibition alleviates oxidative-stress-induced osteoblast apoptosis and dysfunction by enhancing Nrf2/ARE signaling activation, findings that suggest a critical role for the Bach1/Nrf2/ARE regulation axis in osteoporosis progression. Our study suggests that Bach1 may serve as a potential therapeutic target for treating osteoporosis. Graphical abstract: Image 1 Highlights: Bach1 is induced by H2 O2 in osteoblasts. Bach1 inhibition alleviates oxidative damage in osteoblasts. Bach1 regulates osteoblast oxidative damage by Nrf2 signaling. Nrf2 silencing reverses Bach1 inhibition mediated protection effect.